Kurdish women's issues and Kurdish nationalism in Southern Kurdistan - Ali, Dilshad Sabri Ali; Muhyadeen, Rozhan Ahmad Muhyadeen (Sulaimani Journal for Humanities, 2026)
This study is a sociological theoretical perspective that aims to respond to the primary issue, which illustrates the relationship between Kurdish nationalism and women's rights in Southern Kurdistan. This article relies on analytical criticism of the relationship between feminism and nationalism in Southern Kurdistan from the Intersectionality theory. Through this theory, efforts are made to show the struggle of Kurdish women to achieve their rights and their identity through Kurdish nationalism in Southern Kurdistan, in which the main obstacles to participating in society have been gender inequality or other issues, for example, ethnic minority, social class or other issues as intersectionality theory emphasis on it. The study's results demonstrate how nationalism and anti-authoritarian movements paved the way for women to participate alongside men in all areas, such as political, economic and social. As can be seen in this study, Kurdish nationalism has been important for the affirmation of social and political freedom of the Kurdish nation by women in Southern Kurdistan. However, Kurdish nationalist leaders in Southern Kurdistan have not entirely given the rights that women demanded.
Keywords: Intersectionality theory; Feminism; Gender; nationalism; Southern Kurdistan